2017
DOI: 10.1038/srep46650
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rectal nonsteroidal anti-inflammatory drugs for prophylaxis against post-ERCP pancreatitis: a systematic review and meta-analysis

Abstract: Rectal nonsteroidal anti-inflammatory drugs (NSAIDs) are not commonly used clinically for preventing post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. To evaluate the efficacy and safety of NSAIDs for post-ERCP prophylaxis, we systematically reviewed sixteen randomized controlled trials (involving 6458 patients) that compared rectal NSAIDs with placebo or no treatment for post-ERCP pancreatitis prophylaxis updated to August 2016. GRADE framework was used to assess the quality of evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…The results showed that NSAIDs administered pre-ERCP may be more effective than those administered post-ERCP. This result is similar to the conclusion of a meta-analysis in 2017 that incorporates 16 studies [ 40 ]. However, there are different voices on the ideal time of administration [ 43 46 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results showed that NSAIDs administered pre-ERCP may be more effective than those administered post-ERCP. This result is similar to the conclusion of a meta-analysis in 2017 that incorporates 16 studies [ 40 ]. However, there are different voices on the ideal time of administration [ 43 46 ].…”
Section: Discussionsupporting
confidence: 89%
“…No study has compared rectal indomethacin and diclofenac in a head-to-head trial to see if there is any difference in the efficacy between these 2 agents. Previous meta-analysis showed that diclofenac was more effective than other NSAIDs in reducing the incidence of PEP [ 40 , 41 ]. However, one of the studies described only the rectal route of administration [ 40 ], and the other included the study included the rectal 、intravous、intramuscular and oral administration [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also supported by a meta-analysis performed by Puig et al 20. Contrary to this, a more recent meta-analysis performed by Hou et al 21 showed that rectal diclofenac is likely to be more superior than indomethacin and post-ERCP is probably more superior to pre-ERCP. They showed a reduction in the incidence of PEP and a reduction in the severity of PEP.…”
Section: Introductionmentioning
confidence: 77%
“…Oddi sphincter manometry procedures are associated with BP in 25% of cases. The routine using 100mg of indomethacin or diclofenac rectal route, immediately before or after ERCP is indicated routine and significantly reduces the risk of this complication [43][44][45].…”
Section: Surgical and Endoscopic Proceduresmentioning
confidence: 99%